Structural change and environmental Kuznets curves - Jens Horbach (Fondazione Eni Enrico Mattei (FEEM), 2002)
The Environmental Kuznets Curve hypothesis (EKC) postulates an inverted u-shaped curve between important pollutants and per capita GDP analogous to the relationship between in-come inequality and income per capita which has been analysed by Kuznets in 1955. The arti-cle focuses on an empirical analysis of structural change between branches as one major de-terminant of EKCs. The results of a cointegration analysis show that amongst other determi-nants the decline of environmental intensive branches in Germany during the last decades can be econometrically explained by the development of energy prices and the so-called Fourastié hypothesis.
Keywords: O13; Q20; C22; 330; Structural Change; Environment; Umweltbelastung; Sozialprodukt; Strukturwandel; Deutschland; Environmental Kuznets Curve